Challenges and rewards of the electrosynthesis of macroscopic aligned carbon nanotube array/conducting polymer hybrid assemblies. Issue 21 (16th July 2015) - Endrődi, Balazs; Samu, Gergely Ferenc; Fejes, Dora; Németh, Zoltan; Horváth, Endre; Pisoni, Andrea; Matus, Peter Krisztian; Hernádi, Klara; Visy, Csaba; Forró, Laszlo; Janáky, Csaba
ABSTRACT Hybrid assemblies based on conducting polymers and carbon nanomaterials with organized nanoscale structure are excellent candidates for various application schemes ranging from thermal management to electrochemical energy conversion and storage. In the case of macroscopic samples, however, precise control of the nanoscale structure has remained a major challenge to be solved for the scientific community. In this study we demonstrate possible routes to homogeneously infiltrate poly(3‐hexylthiophene), poly(3, 4‐ethylenedioxythiophene), and polyaniline into macroscopic arrays of vertically aligned multiwalled carbon nanotubes (MWCNTAs). Electron microscopic images and Raman spectroscopic analysis (performed along the longitudinal dimension of the hybrid samples) both confirmed that optimization of the electropolymerization circumstances allowed fine tuning of the hybrid structure towards the targeted application. In this vein, three different application avenues were tested. The remarkable anisotropy in both the electrical and thermal conductivity of the nanocomposites makes them eminently attractive candidates to be deployed in thermal management. Thermoelectric studies, aimed to understand the effect of organized nanoscale morphology on the important parameters (Seebeck coefficient, electrical‐, and thermal conductivity) compared to their non‐organized hybrid counterparts. Finally, extraordinary high charge storage capacity values were registered for the MWCNTA/PANI hybrids (500 F g−1 and 1–3 F cm−2). © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1507–1518